The Preparation of Lesson Plans as the Foundation of Instructional Planning in Madrasah Ibtidaiyah - Valya Adila; Isha Nayna Sidni; Nazwa Ramadani; Dina Mardiana; Muhammad Jahlan; Hendra Surya Aditama; Ali Iskandar (The Future of Education Journal, 2026)
Lesson plan (RPP) preparation is a fundamental competency that every teacher must master to ensure effective and purposeful learning in Madrasah Ibtidaiyah (MI). However, in practice, many MI teachers still face challenges in preparing quality lesson plans that are aligned with curriculum demands, student characteristics, and Islamic educational values. This study aims to examine the position, components, principles, and steps of effective RPP preparation as the basis for learning planning in MI. This research employs a qualitative descriptive method with a library research approach, collecting data from scientific journals, books, and relevant curriculum documents. The results indicate that RPP in MI is not merely an administrative document, but serves as a strategic instrument that reflects the teacher’s pedagogical competence. An effective RPP integrates Islamic values with academic competencies and is structured based on observable learning objectives, appropriate learning methods, and formative assessment. The findings also emphasize that teacher quality in lesson planning is directly influenced by content knowledge, procedural knowledge, and the support of academic supervision. This study concludes that strengthening RPP preparation practices in MI requires systematic training, regular supervision, and the development of an integrative RPP model that holistically accommodates the academic and Islamic character dimensions of elementary-level students.